The Influence of Employer Branding Dimension on Interest in Applying a Job: Gen Z Perspective of Students Graduating from the Faculty of Economics, Islamic University of Kalimantan, Muhammad Arsyad Al Banjari: English - Ariani, Gusti Meinar Girda; Wicaksono, Teguh; Herawati, Ana Sofia; Hasanah, Nurul (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to analyze the influence of employer branding dimensions on interest in applying for jobs through the perspective of Gen Z who are students that graduated from the Faculty of Economics. Employer branding is a company strategy in building a positive image as a desirable workplace, which includes several dimensions, such as company reputation, compensation and benefits, career development opportunities, work environment, and balance between personal and work life. Data was collected through a survey of students who had just graduated from the Faculty of Economics at Islamic University of Kalimantan Muhammad Arsyad Al Banjary. The results of the analysis show that all dimensions of employer branding have a significant effect on interest in applying for jobs, especially in the dimensions of company reputation and career development opportunities. This research provides important implications for companies in designing effective employer branding strategies to attract the best talent from new graduates, especially from the Faculty of Economics.